Development of a Smartphone‐Enabled Hypertension and Diabetes Mellitus Management Package to Facilitate Evidence‐Based Care Delivery in Primary Healthcare Facilities in India: The mPower Heart Project. Issue 12 (21st December 2016) - Ajay, Vamadevan S.; Jindal, Devraj; Roy, Ambuj; Venugopal, Vidya; Sharma, Rakshit; Pawar, Abha; Kinra, Sanjay; Tandon, Nikhil; Prabhakaran, Dorairaj
Abstract : Background: The high burden of undetected and undertreated hypertension and diabetes mellitus is a major health challenge worldwide. The mPower Heart Project aimed to develop and test a feasible and scalable intervention for hypertension and diabetes mellitus by task‐sharing with the use of a mobile phone–based clinical decision support system at Community Health Centers in Himachal Pradesh, India. Methods and Results: The development of the intervention and mobile phone–based clinical decision support system was carried out using mixed methods in five Community Health Centers. The intervention was subsequently evaluated using pre–post evaluation design. During intervention, a nurse care coordinator screened, examined, and entered patient parameters into mobile phone–based clinical decision support system to generate a prescription, which was vetted by a physician. The change in systolic blood pressure, diastolic blood pressure, and fasting plasma glucose (FPG) over 18 months of intervention was quantified using generalized estimating equations models. During intervention, 6797 participants were enrolled. Six thousand sixteen participants had hypertension (mean systolic blood pressure: 146.1 mm Hg, 95% CI: 145.7, 146.5; diastolic blood pressure: 89.52 mm Hg, 95% CI: 89.33, 89.72), of which 3152 (52%) subjects were newly detected. Similarly, 1516 participants had diabetes mellitus (mean FPG: 177.9 mg/dL, 95% CI: 175.8, 180.0), of which 450 (30%) subjects were newly detected. The changes in systolic blood pressure, diastolic blood pressure, and FPG observed at 18 months of follow‐up were −14.6 mm Hg (95% CI: −15.3, −13.8), −7.6 mm Hg (CI: −8.0, −7.2), and −50.0 mg/dL (95% CI: −54.6, −45.5), respectively, and were statistically significant even after adjusting for age, sex, and Community Health Center. Conclusions: A nurse‐facilitated, mobile phone–based clinical decision support system‐enabled intervention in primary care was associated with improvements in blood pressure and blood glucose control and has the potential to scale‐up in resource poor settings. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifiers: NCT01794052. Clinical Trial Registry—India: CTRI/2013/02/003412.